2017
DOI: 10.4085/1062-6050-52.11.24
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Screening Methods to Detect Cardiac Disorders in Athletes: An Evidence-Based Review

Abstract: Reference/Citation: Harmon KG, Zigman M, Drezner JA. The effectiveness of screening history, physical exam, and ECG to detect potentially lethal cardiac disorders in athletes: a systematic review/meta-analysis. J Electrocardiol. 2015;48(3):329-338.Clinical Question: Which screening method should be considered best practice to detect potentially lethal cardiac disorders during the preparticipation physical examination (PE) of athletes?Data Sources: The authors completed a comprehensive literature search of MEDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Therefore, it is imperative that ATs have a better understanding of not only individual-level and population-level public health concepts, but also how these initiatives impact the cost of care and influence one another. From the population health dimension, measures of health/functional status, 57,58 assessing risk, 59,60 understanding the incidence and prevalence of diseases, 61,62 and appreciating the years of potential life lost 63,64 are all relevant standards for ATs to be competent in as they deliver patient care.…”
Section: Public Health: Current Realities and Future Directionmentioning
confidence: 99%
“…Therefore, it is imperative that ATs have a better understanding of not only individual-level and population-level public health concepts, but also how these initiatives impact the cost of care and influence one another. From the population health dimension, measures of health/functional status, 57,58 assessing risk, 59,60 understanding the incidence and prevalence of diseases, 61,62 and appreciating the years of potential life lost 63,64 are all relevant standards for ATs to be competent in as they deliver patient care.…”
Section: Public Health: Current Realities and Future Directionmentioning
confidence: 99%
“…1 Although there is a concern that ECGs produce a high number of false-positive results leading to unnecessary diagnostic testing, studies have shown that the adoption of modern, strict ECG criteria have lowered false-positive rates to 6% compared to history at 8% and physical examination at 10%. 1,3 The studies in this review highlight that the rate of false-positives are greater with a history and physical examination model. Another consideration is the cost component associated with the implementation of ECG to pre-participation screenings.…”
Section: Clinical Bottom Linementioning
confidence: 99%
“…2 This position statement also indicated the need for continued research on cardiac screening methods to "improve the ability to identify at-risk individuals in a cost-effective manner" with an acceptable false-positive rate to be utilized as a screening method to reduce the rates of sudden cardiac death (SCD). 3 In the United States between 2014-2018, 50% of sudden cardiac arrest cases occurred in Caucasian competitive athletes with 55% (n=88/164) of those cases resulting in survival. 4 However, the survival rates for African American athletes was only 25% (n=39/109) with an accompanied incidence rate for a male, African American, National Collegiate Athletic Association (NCAA) Division 1 basketball player at 1:2087.…”
mentioning
confidence: 99%
“…Cardiac pre-participation screening has been implemented among professional sports organizations for identification of athletes at risk for cardiac disorders to prevent sudden cardiac events. NATA and the American Heart Association (AHA) have recommended a complete history and physical exam, with an emphasis on family history, as 80% of individuals who experience sudden cardiac death are asymptomatic themselves prior to the event [30]. Electrocardiograms (EKG) are also completed as part of entrance physicals league wide; however, the use of EKG is controversial at other levels of sport.…”
Section: Cardiac Screeningmentioning
confidence: 99%